Our brightly‐lit future: Exploring the potential for astrotourism in Khajuraho (India). (25th January 2022) - Khetrapal, Neha; Bhatia, Divya
Abstract : The night skies have traditionally offered a means of navigation, symbolized the gods, and inspired architecture and creative planning. With the advent of urbanization and the consequent increase in artificial light at night (ALAN), humans have severed their connection with the skies. Some suggest that "astrotourism" may serve as a viable means of re‐establishing this relationship. While astrotourism is usually used for referring to activities that revolve around stargazing with "aided" or "naked" eyes, we highlight that there is scope to include exploration of historic monument ensembles and night‐time storytelling as a part of astrotourism. Focusing on Khajuraho, we further underscore that ALAN should be replaced with intelligent night lighting strategies to maximize the night‐time travel experience for those who take inspiration from the dark skies to reconstruct the historical significance of heritage. As we gradually revitalize our relations with the nocturnal environment, it is hoped that the night skies will infuse our social practices, creative imagination, and historical appreciation with a new vigour. Key Messages: The relationship that ancient people shared with the night skies has been lost and we are moving further away due to artificial light at night (ALAN). There is still potential for the conservation of night skies by developing astrotourism and this is highlighted with the help of a UNESCO world heritage site in central India. The hope is that astrotourism will allow people to experience transcendence from their position as terrestrial beings and to be a part of the larger cosmos. Un futur brillant: Les possibilités de l'astrotourisme à Khajuraho (Inde): La voûte étoilée a traditionnellement offert un moyen de navigation, symbolisé les dieux et inspiré l'architecture et les aménagements créatifs. Avec l'avènement de l'urbanisation et l'augmentation conséquente de la lumière artificielle durant la nuit (LADN), les humains ont largement rompu leur relation avec le ciel nocturne. Dans ce contexte, « l'astrotourisme » peut servir de moyen viable pour rétablir cette relation. Bien que l'astrotourisme soit habituellement utilisé en référence à l'observation d'étoiles à « l'aide d'instruments » ou à « l'oeil nu », nous proposons d'inclure l'exploration d'ensembles de monuments historiques, accompagnée de narrations nocturnes, dans le cadre des pratiques d'astrotourisme. En mettant l'accent sur Khajuraho, nous soulignons de plus que la LADN devrait être remplacée par des stratégies d'éclairage nocturne intelligent afin de maximiser l'expérience des voyages de nuit pour les personnes qui trouvent leur inspiration dans les cieux étoilés pour reconstruire le sens du patrimoine. Alors que nous réactualisons graduellement nos relations avec l'environnement nocturne, il est à espérer que celui‐ci imprègnera nos pratiques sociales, notre imagination créatrice et notre appréciation historique d'une nouvelle vigueur.